2019
DOI: 10.1186/s12879-019-4183-0
|View full text |Cite
|
Sign up to set email alerts
|

Utility of oral fluid samples for hepatitis B antibody detection in real life conditions

Abstract: Background Hepatitis B virus (HBV) testing in oral fluid samples may provide advantages in diagnosis, screening or prevalence studies, especially among individuals with venous access difficulties. This study aims to optimize one commercially available assay for detecting total anti-HBc marker in oral fluid samples and to evaluate its utility under real life conditions in different settings for the purposes of prevalence and diagnostic studies. Methods Oral fluid was col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Saliva samples could be useful specimens since collection is less invasive, safer and allows the option of self-collection. Saliva samples have been evaluated for detecting viral hepatitis markers ( 2 , 3 ), however there is a lack of studies about usefulness of these samples for detecting SARS CoV-2 in hepatitis infected individuals and non-severe cases of COVID-19. The saliva collection can be safer than NPS samples, especially for those patients that presenting decompensated cirrhosis or other severe sequels, like hepatocarcinoma.…”
mentioning
confidence: 99%
“…Saliva samples could be useful specimens since collection is less invasive, safer and allows the option of self-collection. Saliva samples have been evaluated for detecting viral hepatitis markers ( 2 , 3 ), however there is a lack of studies about usefulness of these samples for detecting SARS CoV-2 in hepatitis infected individuals and non-severe cases of COVID-19. The saliva collection can be safer than NPS samples, especially for those patients that presenting decompensated cirrhosis or other severe sequels, like hepatocarcinoma.…”
mentioning
confidence: 99%
“…[19] Regarding SARS-CoV-2, only a study procedure aimed to analyse IgG, IgM and IgA in changed biological fluids including self-collected saliva for rapid SARS-CoV-2 diagnosis has been published [20] . Viral antibodies have been noticed in saliva and the immunisation status of measles, rubella, mumps and hepatitis can be confirmed by analysing IgG, IgM and IgA in oral fluids [18] . Though, there are so far no outcomes describing the presence of antibodies against SARS-CoV-2 in human saliva.…”
Section: Salivary Antibiodies Against Covid-19mentioning
confidence: 98%
“…Viral antibodies have been spotted in saliva and the immunisation status of measles, rubella, mumps and hepatitis can be tested by analysing IgG, IgM and IgA in oral fluids [18] . In addition to RT-PCR-based RNA detection of SARS-CoV-2, initially studies have been reported, capable results for the finding of IgM and IgG against SARS-CoV-2 in serum/plasma samples of patients with SARS-CoV-2.…”
Section: Salivary Antibiodies Against Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“…Saliva sampling as a noninvasive method (ie, it does not cause disturbance) for SARS-CoV-2 antibody measurements and is an elegant approach to rapidly assess the prevalence of SARS-CoV-2 infection in vulnerable cohorts at numbers appropriate for epidemiologic investigations [ 14 ]. Studies have reported the use of saliva not only for detection of respiratory viruses, including coronaviruses and SARS-CoV-2 [ 15 ], but also for detection of antibodies against measles, rubella, mumps, and hepatitis [ 16 - 18 ]. The number of seroprevalence studies benefiting from noninvasive saliva sampling is increasing [ 19 ].…”
Section: Introductionmentioning
confidence: 99%